Dual-system Involvement: Exploring the Overlap Between Domestic and Family Violence and Child Maltreatment Perpetration - Gilbert, Brigitte (Journal of interpersonal violence, 2022)
This longitudinal population-based study aimed to understand the dual-system involvement of males who engage in domestic and family violence (DFV) and child maltreatment perpetration. Specifically, this study investigates the prevalence of male perpetration of DFV, child maltreatment, and dual-system involvement, and compares the frequency and nature of perpetration by males with single-system contact and males with dual-system contact. The effect of race (Indigenous Australian/non-Indigenous Australian) and parental status on dual-system involvement is also examined. This study utilizes data from the Queensland Cross-sector Research Collaboration repository. These data contain each contact an individual male born in 1983 or 1984 had with the Queensland civil court system as a respondent to a domestic violence order (DVO) and the Queensland statutory child protection system, where, after an investigation, they were identified as the person responsible for substantiated harm to a child. The results from the study show a high level of overlap between males who perpetrate DFV and child maltreatment. Of males identified as being responsible for substantiated harm to a child, 58% have also been a respondent of a DVO, and approximately 16% of male DVO respondents were identified as being responsible for substantiated harm to a child. Differences were found in the frequency and nature of perpetration by males with dual-system involvement compared to those with single-system contact for either DFV or child maltreatment. Our results also show differences for Indigenous status, parental status, number of maltreatment events, harm type, number of DVOs, and number of breaches of a DVO. The implications of this study for both policy and practice are discussed.